2011
DOI: 10.1525/auk.2011.10266
|View full text |Cite
|
Sign up to set email alerts
|

Nest Survival and Density of Cackling Geese (Branta Hutchinsii) Inside and Outside a Ross's Goose (Chen Rossii) Colony

Abstract: The influence of heterospecifics on successful avian reproduction remains poorly understood, despite the role that such relationships may play in the evolution of reproductive strategies. We estimated nest survival of Cackling Geese (Branta hutchinsii)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
20
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 45 publications
3
20
2
Order By: Relevance
“…Gleason et al (2004) suggested that Southern James Bay Population Canada Geese experience reduced nest survival when nesting among Snow Geese, which would predict low density of EPP Canada Goose nests in areas with high density of nesting Snow Geese. Baldwin et al (2011) found that Cackling Geese generally experienced higher nest survival when nesting within a colony of Snow and Ross's (C. rossii) Geese than outside the colony. However, at the same time, Cackling Geese with very high densities of Snow and Ross's Geese nests within 30 m had very low nest survival.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Gleason et al (2004) suggested that Southern James Bay Population Canada Geese experience reduced nest survival when nesting among Snow Geese, which would predict low density of EPP Canada Goose nests in areas with high density of nesting Snow Geese. Baldwin et al (2011) found that Cackling Geese generally experienced higher nest survival when nesting within a colony of Snow and Ross's (C. rossii) Geese than outside the colony. However, at the same time, Cackling Geese with very high densities of Snow and Ross's Geese nests within 30 m had very low nest survival.…”
Section: Discussionmentioning
confidence: 98%
“…Intensive foraging by large populations of migrating and breeding Snow Geese (C. caerulescens) can dramatically alter sub-arctic vegetation (Jano et al 1998;Jefferies and Rockwell 2002). Less is known about the direct or indirect effects of this growing breeding population on other species, particularly sympatrically nesting EPP Canada Geese (see Gleason et al 2004 re: Southern James Bay Population Canada Geese) and Cackling Geese (B. hutchinsii; Baldwin et al 2011;Kellett and Alisauskas 2011).…”
mentioning
confidence: 99%
“…Additionally, some birds nesting in a goose colony could be afforded protection from satiated predators (Baldwin et al. , Kellett and Alisauskas ), but this benefit may be offset by interspecific conflicts (Baldwin et al. ).…”
Section: Discussionmentioning
confidence: 99%
“…, Kellett and Alisauskas ), but this benefit may be offset by interspecific conflicts (Baldwin et al. ). Through fecal deposition, geese could also be altering wetland water chemistry (Mariash et al.…”
Section: Discussionmentioning
confidence: 99%
“…On Akimski Island, Nunavut, Canada geese experienced reduced nest survival when nesting among lesser snow geese [16]. In a different study, cackling geese ( Branta huchinsii ) showed evidence, in part, supporting a protective association with higher nest success for cackling goose nests within aggregations of nesting Ross’s geese [17]. However, cackling goose nest survival was reduced when there were very high densities of Ross’s goose nests within 30 m. A recent range-wide evaluation of nesting Canada geese and lesser snow geese along western Hudson Bay and Cape Churchill [18] identified landscape-scale patterns in the distribution of breeding EPP Canada geese consistent with the findings in the cackling goose-Ross’s goose study [17].…”
Section: Introductionmentioning
confidence: 99%